2014
DOI: 10.1177/1578.17204
|View full text |Cite
|
Sign up to set email alerts
|

Practice Patterns for Oropharyngeal Cancer in Radiation Oncology Centers of Turkey

Abstract: Across all the centers there were small differences in the pretreatment evaluation of patients with oropharyngeal cancer. The greatest difference was in the technical delivery of radiation, with most of the centers using conformal radiotherapy despite the increasing availability of intensity-modulated radiotherapy. The use of chemotherapy has more readily adopted the current international standards in the treatment of oropharyngeal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Previous studies have indicated that reinterpretation of imaging in the setting of a multidisciplinary cancer center has a significant effect on staging, management, and prognosis. 9,23,24 As our data shows, roughly half of the patients evaluated with staging changes had this change made in the context of review by a multidisciplinary tumor board.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Previous studies have indicated that reinterpretation of imaging in the setting of a multidisciplinary cancer center has a significant effect on staging, management, and prognosis. 9,23,24 As our data shows, roughly half of the patients evaluated with staging changes had this change made in the context of review by a multidisciplinary tumor board.…”
Section: Discussionmentioning
confidence: 92%
“…7 When determining what led to the difference, studies have implicated factors such as the volume of treatments rendered at the facilities, 8 technical expertise, 9 as well as multidisciplinary team management. 3,9 In one study examining 1195 Medicare patients with advanced head and neck cancer treated at high-and low-volume centers, patients were found to have nearly statistically significant better survival at high volume hospitals despite no association found in receiving multimodality therapy. 10 This implies that survival-promoting features of high volume hospitals extend beyond guideline adherence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation